Delayed Diagnosis of Langerhans Cell Histiocytosis Presenting With Thyroid Involvement and Respiratory Failure: A Pediatric Case Report. Issue 8 (November 2020) - He, Yingyi; Xie, Jianling; Zhang, Hui; Wang, Jiayi; Su, Xiaoling; Liu, Dianyue
Abstract : Langerhans cell histiocytosis (LCH) is a rare disease with localized to disseminated clinical features. Thyroid involvement in LCH is rare and presenting as either a single-organ or multisystem disease, it is usually misinterpreted as another thyroid disorder. Therefore, the LCH diagnosis is often delayed. We report a pediatric case of LCH with thyroid involvement as the initial clinical manifestation progressing to respiratory failure. Clinicians should note insidious extrathyroidal laboratory abnormalities and consider infiltrative thyroid diseases, such as LCH. Systematic clinical and laboratory investigations are needed to prevent delayed diagnosis because the classic features of LCH may become evident only over time.